2014
DOI: 10.2304/power.2014.6.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Touch, Fear, and Child Protection: Immoral Panic and Immoral Crusade

Abstract: This contrarian article revisits the concept of moral panic as applied by the author in previous writing on intergenerational touch, child abuse, and child protection, in terms of its current utility in analysing related policy and practice. Engagement in the Economic and Social Research Council (ESRC) Seminar Series, Revisiting Moral Panics prompted a reconsideration of the author's deployment of the concept, supported by some historic and more recent theoretical debates. To this end the article: refers to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…This study joins a small group of studies from the United Kingdom [4,16,[29][30][31] and the United States [6,9,32,33] that indicated that guidelines for protecting children from CSA and staff from wrongful allegations are pervasive at British and American preschool institutions. These studies 1 The study is called The Guideline Study 2012, in Danish, Retningslinjeundersøgelsen 2012.…”
Section: Introductionmentioning
confidence: 91%
“…This study joins a small group of studies from the United Kingdom [4,16,[29][30][31] and the United States [6,9,32,33] that indicated that guidelines for protecting children from CSA and staff from wrongful allegations are pervasive at British and American preschool institutions. These studies 1 The study is called The Guideline Study 2012, in Danish, Retningslinjeundersøgelsen 2012.…”
Section: Introductionmentioning
confidence: 91%
“…There is a need to work on this bodily closeness, particularly in today's society, where social and mass media do not promote ideal personal development. (Christopher, male, week 2) 3 Students from Spanish-speaking countries often use the term 'profe' to refer to teachers at all levels (i.e., primary, secondary and tertiary) in an affectionate way. The term comes from 'profesor' but it does not refer to the 'professor' title used within Anglophone academia.…”
Section: Acknowledging Emotions and Feelingsmentioning
confidence: 99%
“…Within Physical Education (PE), physical contact is often considered 'normal' or embedded in the profession [1][2][3]. PE teachers utilise different techniques that involve bodily touch connected to specific traditional purposes such as guidance, encouragement and safety [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We argued that the wide, pervasive and moral crusader-led discourse of safeguarding and child protection has created a 'folk devil' and moral panic (Cohen, 1999;Piper, 2014), escalating fear among coaches and radically disturbing the role of the coach through the adoption of questionable defensive and self-protective practices (Taylor et al 2014). This has corollary implications and often deleterious consequences for the development of 2 sound intergenerational relationships between coach and athlete in youth sport and physical education, alongside collateral negative effects in adult sport.…”
Section: Introductionmentioning
confidence: 99%